Molecular detection of bacterial endosymbionts in Acanthamoeba spp.: a preliminary study - Faizah Mohd Hanapiah,; Anisah Nordin,; Yusof Suboh,; Noraina AR,; Adibah MR, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Acanthamoeba spp. is a free-living amoeba commonly found in the environment. It is the causative agent of Acanthamoeba keratitis (AK) and granulomatous amoebic encephalitis (GAE). This amoeba is also a host to various bacteria including pathogenic ones such as Mycobacterium, Legionella, Pseudomonas and Methicillin-resistant Staphylococcus aureus (MRSA). In light of this information, a study was undertaken to detect these bacterial endosymbionts in Acanthamoeba spp. isolated from air-conditioning outlets in wards and operating theatres in Universiti Kebangsaan Malaysia Medical Centre (UKMMC). The presence of these bacteria was screened using primer pair targeting each genus and further confirmed by sequencing analysis. Twenty-nine (80.56 %) Acanthamoeba isolates were found to contain targeted bacterial endosymbiont with at least one genus of bacteria per isolates. Mycobacterium spp. (82.76 %) were the most common bacteria detected, followed by Legionella spp. (65.52 %) and Pseudomonas spp. (62.07 %). No MRSA were detected in any isolates used in this study. Most of the Mycobacterium endosymbionts were non-tuberculous mycobacteria, while only two were part of Mycobacterium tuberculosis complex group. We conclude that most Acanthamoeba have the potential to host various pathogenic bacteria. However, the implication on the pathogenicity of both organisms remains unclear and further investigations are needed.